Serum Osteoprotegerin Is a Potential Biomarker of Insulin Resistance in Chinese Postmenopausal Women with Prediabetes and Type 2 Diabetes - Peng Duan; Min Yang; Meilin Wei; Jia Liu; Ping Tu (International Journal of Endocrinology)
The aim of this study is to investigate the circulating OPG levels in postmenopausal women with diabetes and prediabetes and explore the relationships between serum OPG and insulin resistance. A total of 271 unrelated Chinese postmenopausal women were recruited in this study. The subjects were divided into type 2 diabetes mellitus (T2DM) group (n=93), impaired glucose regulation (IGR) (n=90), and normal glucose regulation group (NGR) (n=88), according to different glucose regulation categories. Serum OPG levels were measured by enzyme-linked immunosorbent assay. The serum OPG concentration in NGR group, 151.00 ± 45.72 pg/mL, was significantly lower than that in IGR group (169.28 ± 64.91 pg/mL) (p=0.031) and T2DM group (183.20 ± 56.53 pg/mL) (p<0.01), respectively. In multiple linear regression analysis, HOMA-IR, age, 2hPG, AST, ALP, and eGFR were found to be independent predictors of OPG. Increased serum OPG levels (OR = 1.009, p=0.006) may be a risk factor for insulin resistance. The present study suggests that OPG might be implicated in the pathogenesis of diabetes and is a potential biomarker of insulin resistance in subjects with diabetes and prediabetes.